Effect of thermal oxidation on corrosion resistance of Ti-8Mo4Nb-2Zr alloy for biomedical application - Siti Norsuraya Hussain (2021)
Titanium and titanium alloys are widely used in a variety of engineering applications. Medical device manufacturers have also benefited from the outstanding properties of titanium alloys. However, titanium alloys are weak in meeting all of the clinical requirements for biomedical implants. Issues such as metal sensitivity associated with high levels of metal ion release triggered by corrosion effects remain critical concerns. Hence, the implant material surface has a strong role in the responses to the biological environment the implant can be stimulated in contact with the bone. In order to improve the biological and tribological properties of implant materials, surface modification needed to be made. Thermal oxidation is one of the surface modification techniques to enhance the corrosion performance of titanium alloys. This technique is excellent for forming a thicker oxide layer on Ti and its alloys to achieve optimum corrosion resistance. In the present study, thermal oxidation of Ti-8Mo-4Nb-2Zr alloy was explored. Hence, experiments were carried out to investigate the effective combination of surface modification parameters and evaluate performance corrosion behaviour in terms of their suitability with the Ti-8Mo-4Nb-2Zr alloy surface for biomedical implants applications. Process thermal oxidation was carried out at 500, 600 and 700C for three different durations of 6, 12 and 24 hours. It was found that particles of oxides formed were noticeably larger after oxidation at an increased temperature of 600C and 700C. The increase in temperature resulted in the formation of compact particles in the oxide layer. A phase analysis showed that the phase contents of the oxide layer showed a strong dependence on treatment conditions with a predominance of the rutile phase over the anatase phase at temperatures > 500C and for time periods > 6h. Improved corrosion resistance had been achieved of these alloys using thermal oxidation. EIS was employed to measure the corrosion resistance of the Ti-8Mo-4Nb-2Zr alloys in simulated physiological solutions of a wide pH range (namely 7.4 pH) at 37C, and the best results were obtained for the alloys at 700C. A more positive Ecorr value (-0.125 V) and a lower Icorr value (2.583 A x 10-6) were observed for the thermally oxidized Ti-8Mo-4Nb-2Zr alloys when compared with the untreated alloy. This finding, the oxide scale on the examined alloy efficiently enhances can increase the corrosion resistance of the implant material.